Sub-THz Characterisation of Monolayer Graphene - Ehsan Dadrasnia; Sujitha Puthukodan; Vinod V. K. Thalakkatukalathil; Horacio Lamela; Guillaume Ducournau; Jean-Francois Lampin; Frédéric Garet; Jean-Louis Coutaz (Journal of Spectroscopy)
We explore the optical and electrical characteristics of monolayer graphene by using pulsed optoelectronic terahertz time-domain spectroscopy in the frequency range of 325–500 GHz based on fast direct measurements of phase and amplitude. We also show that these parameters can, however, be measured with higher resolution using a free space continuous wave measurement technique associated with a vector network analyzer that offers a good dynamic range. All the scattering parameters (both magnitude and phase) are measured simultaneously. The Nicholson-Ross-Weir method is implemented to extract the monolayer graphene parameters at the aforementioned frequency range.